A Mini-Review on the Epidemiology of Canine Parvovirus in China - Qi, Shanshan; Zhao, Jianjun; Guo, Donghua; Sun, Dongbo (Frontiers in Veterinary Science, 2020)
Canine viral diarrhea is a severe disease in dogs worldwide. The role of canine parvovirus (CPV) in canine viral diarrhea is a common dog health problem attracting major concern from veterinarians and dog owners across China. In this mini-review, we summarize CPV epidemiology in China, including the origin, prevalence, co-infection and genetic evolution of the virus. The review revealed that correlation between CPV infection and seasonality, dog's age/gender/breed/vaccination; CPV was the main causative agent of canine diarrhea in Northeast China, and that co-infection with other pathogens was a common occurrence; the predominant CPV epidemic strains were the new CPV-2a, and CPV-2c has shown significant growth trends since 2010. This mini-review will provide valuable information for CPV infections across China and other countries.